Managing and eradicating wildlife tuberculosis in New Zealand - Warburton, B (N Z Vet J, 2015)
Tuberculosis (TB) due to Mycobacterium bovis infection was first identified in brushtail possums (Trichosurus vulpecula) in New Zealand in the late 1960s. Since the early 1970s, possums in New Zealand have been controlled as part of an ongoing strategy to manage the disease in livestock. The TB management authority (TBfree New Zealand) currently implements three strategic choices for disease-related possum control: firstly TB eradication in areas selected for eradication of the disease from livestock and wildlife, secondly Free Area Protection in areas in which possums are maintained at low densities, normally along a Vector Risk Area (VRA) boundary, and thirdly Infected Herd Suppression, which includes the remaining parts of VRA where possums are targeted to minimise the infection risk to livestock. Management is primarily through a range of lethal control options. The frequency and intensity of control is driven by a requirement to reduce populations to very low levels (usually to a trap-catch index below 2%), then to hold them at or below this level for 5–10 years to ensure disease eradication.Lethal possum control is implemented using aerial- and ground-based applications, under various regulatory and operational constraints. Extensive research has been undertaken aimed at improving the efficacy and efficiency of control. Aerial applications use sodium fluoroacetate (1080) bait for controlling possums over extensive and rugged areas of forest that are difficult to access by foot. Ground-based control uses a range of toxins (primarily, a potassium cyanide-based product) and traps. In the last 5 years there has been a shift from simple possum population control to the collection of spatial data on possum presence/absence and relative density, using simple possum detection devices using global positioning system-supported data collection tools, with recovery of possum carcasses for diagnostic necropsy. Such data provide information subsequently used in predictive epidemiological models to generate a probability of TB freedom.The strategies for managing TB in New Zealand wildlife now operate on four major principles: firstly a target threshold for possum population reduction is defined and set, secondly an objective methodology is applied for assessing whether target reductions have been achieved, thirdly effective control tools for achieving possum population reductions are used, and fourthly the necessary legislative support is in place to ensure compliance. TBfree New Zealand's possum control programme meets these requirements, providing an excellent example of an effective pest and disease control programme.